Behind closed doors: How roommate and staff relationships shape Chinese international students’ belonging in residence halls - Yang, Haishan (Journal of International Students, 2025)
This phenomenological qualitative study examines the impact of both structured and unstructured interactions on the sense of belonging among first-year Chinese international students (CIS) in U.S. residence halls. Guided by Hurtado’s (2012) diverse learning environments and Yao’s (2014) literature on international student belonging, this study focuses on roommate relationships and residential staff engagement. Fifteen interviews revealed that belonging was more influenced by interactional processes than by the nationality of the roommate(s). Common patterns included cultural proximity, interaction quality, and opportunities to resolve conflicts. Staff who were visible, approachable, and responsive strengthened their sense of belonging through outreach and policy. Language was a cross-cutting factor affecting participation in and perceptions of residential experiences in both contexts. Situated in a post-COVID-19 context of social fragmentation, the study reframes belonging as an ongoing, context-dependent process influenced by peer relations and institutional climates.